2004
DOI: 10.1111/j.1467-842x.2004.tb00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequality: Social inequality in perceived oral health among adults in Australia

Abstract: Objective: To establish population estimates of self‐assessed tooth loss and subjective oral health and describe the social distribution of these measures among dentate adults in Australia. Methods: Self‐report data were obtained from a nationally representative sample of 3,678 adults aged 18–91 years who participated in the 1999 National Dental Telephone Interview Survey and completed a subsequent mail survey. Oral health was evaluated using (1) self‐assessed tooth loss, (2) the 14‐item Oral Health Impact Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(86 citation statements)
references
References 23 publications
8
71
0
7
Order By: Relevance
“…Our stratified results reflect these generational differences. The results of the analyses agree with previous reports in which there were large differences in missing teeth by age, with much steeper social gradients in older age groups (Sanders and Spencer, 2004). Likewise, the differences by age groups with regard to DMFT were also large.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our stratified results reflect these generational differences. The results of the analyses agree with previous reports in which there were large differences in missing teeth by age, with much steeper social gradients in older age groups (Sanders and Spencer, 2004). Likewise, the differences by age groups with regard to DMFT were also large.…”
Section: Discussionsupporting
confidence: 89%
“…Wamala and colleagues (2006) reported that increased levels of socio-economic disadvantage were associated with decreased use of dental services and poorer oral health among Swedish adults. Previous research in Australia demonstrated income inequalities with regard to edentulism (Sanders and Spencer, 2004), while in the United Kingdom, social gradients with respect to untreated dental disease in both children and adults have been reported (Watt and Sheiham, 1999).…”
mentioning
confidence: 96%
“…This method has been previously shown to have good reliability. 31 In both arches, people with high fear had more teeth missing than people with low fear and conversely, therefore, fewer teeth remaining than people with low fear (Fig 4). These results were statistically significant for both the maxillary (F=26.3,…”
Section: Resultsmentioning
confidence: 92%
“…Oral diseases exhibit a social gradient. 9,10 Hence the shift from the CDHP to the 30% rebate also represented a shift from funding dental care services for those with the greatest oral health care needs to those with moderate or low need. This represents a shift in funding from population subgroups that had the potential to achieve significant gains in oral health status, to Restrict 30% rebate for all singles and $31.5m families on incomes of less than $100,000 per year those that would produce modest gains.…”
Section: A Public Health Perspective On the 30% Rebatementioning
confidence: 99%